Incentivos e barreiras ao teste anti-HIV na população geral residente em uma metrópole do Nordeste brasileiro : resultados de um inquérito populacional - Freire, Deborah Gurgel (2013)
This study aimed to identify the incentives and barriers that interfere to perform the HIV test and to explore which individual, programmatic and behavioral factors associated with HIV testing in the general population over 18 years. Sectional study conducted with the general population residing in Fortaleza, 2011 period. The study included 349 people men and women, with 18 full years or more. The sample was randomly selected based on population data from the city, the population was selected by conglomerate with how the seven regional executive of Fortress basis. From the distribution of inhabitants in each region were selected neighborhoods with a higher proportion of inhabitants and from this ratio, the amount of people to be interviewed by district was established. The interviews were conducted in the homes of respondents, within 4 weeks (05/07/2011 to 29/07/2011). The shifts were morning (08h -12h) and late (14h-18h). We used a structured questionnaire inserted in a pocket computer (Pocket PC). Related to socio-demographic, economic status, access to health services, knowledge about STD/AIDS, sexual behavior, HIV testing, violence and alcohol and drug data were collected . Hierarchical bivariate and multivariate analysis was performed using STATA ® 11.0 software. Of the 349 participants, 208 (59.6 %) did not undergo HIV testing. In the hierarchical multivariate analysis, protective factors being female and having a partner were for HIV testing. The other variables , being 50 years or more , not having heard of HIV testing , does not know where the HIV testing , condom not receive and have never donated blood in life were significantly associated with not performing testing anti - HIV. Behavioral factors were not associated with outcome. Do not see reason and find that no risk for HIV infection were barriers for this population is not carried out the test. The certainty of not being infected served as an incentive barrier to testing, indicating the lack of knowledge about the disease and therefore the lack of perception of risk to HIV/AIDS. The findings also indicate the need to make appropriate strategies to increase the supply and distribution of services offered anti - HIV systematically test for the general population, including men. It also reinforces the need for more training for health professionals in order to protect the test results.